2017
DOI: 10.1039/c7fo00702g
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a single serving of red raspberries per day reduces metabolic syndrome parameters in high-fat fed mice

Abstract: Using an animal model for diet-induced metabolic disease, we have shown previously that the addition of raspberry juice concentrate (RJC) and raspberry puree concentrate (RPC) at a level of 10% of kcal, equivalent to four servings per day, to an obesogenic high-fat, western-style diet (HF) significantly reduced body weight gain, serum resistin levels, and altered the expression of hepatic genes related to lipid metabolism and oxidative stress. This study was designed to examine the effect of a lower level of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…bioactive molecules that induce metabolic improvement [31]. Recently, Zhao et al reported metabolic benefits of consuming RR by supplementing with a freeze-dried powder of whole RR fruits containing ~1% of polyphenols in gallic acid equivalent (GAE).…”
Section: Discussionmentioning
confidence: 99%
“…bioactive molecules that induce metabolic improvement [31]. Recently, Zhao et al reported metabolic benefits of consuming RR by supplementing with a freeze-dried powder of whole RR fruits containing ~1% of polyphenols in gallic acid equivalent (GAE).…”
Section: Discussionmentioning
confidence: 99%
“…Of the identified animal studies utilizing whole RR as a treatment for the consequences of a HFD, three studies assessed markers of hepatic steatosis (Table 2). A HFD diet induced ectopic lipid accumulation in the liver of WT mice [35,37], whereas RR produced a significant decrease in hepatic lipid droplets but not total TG in liver tissue, while RPC and RJC decreased liver lipid levels, although not to levels expressed by mice fed a LFD [35,37]. RPC and RJC significantly increased hepatic gene expression of TG catabolism and RJC alone showed increased expression of genes protective against oxidative stress in the liver [37].…”
Section: Effects Of Rr Supplementation On Hepatic Steatosismentioning
confidence: 93%
“…Insulin resistance promoted by a HFD was improved with RR supplementation, albeit only partial restoration of insulin signaling in IngWAT was seen [36]. Raspberry juice concentrate (RJC) was effective in lowering insulin levels raised due to a HFD, but not in lowering elevated fasting glucose levels [37]. Wild type (WT) mice fed a standard chow diet benefited from RR supplementation through induced insulin signaling [35].…”
Section: Effects Of Rr Supplementation On Glucose Handling and Insulin Signalingmentioning
confidence: 99%
See 2 more Smart Citations